Yield productivity test and morphological characterization of 19 sorghum lines resulted from mutation breeding. Issue 1 (April 2020) - Indriatama, Wijaya M.; Garnita, Galuh S.; Setiadi, Teguh; Sihono; Human, Soeranto
Abstract: Sorghum has high potential and prospective to be cultivated and developed, along with increasing food and energy needs in Indonesia. Sorghum mutation breeding aimed to increase the variation, improve the yield and quality as food, raw materials bioethanol (energy) and animal feed. Yield productivity tests and morphological characterization play an important role in the preparation of adaptation tests as well as identifying character variations for the release of crop varieties. The research aims to test the yield productivity and characterize 19 sorghum mutant lines. The research was held from March to June 2016 at the Cibadak Research Station, BB-Biogen, Cipanas. The study used Augmented Design with 19 mutant lines (GHP-21, GHP-22, GHP-24, GH-25, GH-26, GH-27, GH-28, GH-29, GH-30, GH-31, GH-32, GH-33, GH-34, GH-35, GH-36, GH-37, GH-38, GH-39, and GH-40) and 3 national sorghum varieties as Control (Samurai-1, Samurai-2 and Super 2) as treatments. The observed parameters include plant height, number of leaves, stem diameter, time to flowering, panicle length, panicle weight, dry panicle weight, and a thousand seed weight. As for characterization, additional parameters were observed, including observations on the leaves, pistil, husk, panicle, and seeds. The results showed a noticeable difference in all the agronomic characters observed. There is GH-25 mutant line with the highest stem. The GH-40 line shows the earliest ripening. The GH-34 line saw the largest diameter. The GH-35 mutant line has the longest panicles. For the production observation parameters; panicles weight, dried panicles weight, and a thousand seeds weight, GH-33 line, GH-31 line, and GH-27 line have had the best results. Characterization results suggest that 19 sorghum-observed mutant lines have a sufficiently high degree of morphological similarity. The cluster analysis demonstrated by the level of similarity by 86%.